Deterioration of eggshell quality in laying hens experimentally infected with H9N2 avian influenza virus. (December 2016) - Qi, Xuefeng; Tan, Dan; Wu, Chengqi; Tang, Chao; Li, Tao; Han, Xueying; Wang, Jing; Liu, Caihong; Li, Ruiqiao; Wang, Jingyu
Abstract This study aimed to determine the mechanism by which H9N2 avian influenza virus (AIV) affects eggshell quality. Thirty-week-old specific pathogen free egg-laying hens were inoculated with the chicken-origin H9N2 AIV strain (A/Chicken/shaanxi/01/2011) or with inoculating media without virus by combined intraocular and intranasal routes. The time course for the appearance of viral antigen and tissue lesions in the oviduct was coincident with the adverse changes in egg production in the infected hens. The viral loads of AIV have a close correlation with the changes in the uterus CaBP-D28k mRNA expression as well as the Ca concentrations in the eggshells in the infected hens from 1 to 7 days post inoculation (dpi). Ultrastructural examination of eggshells showed significantly decreased shell thickness in the infected hens from 1 to 5 dpi (P  < 0.05). Furthermore, obvious changes in the structure of the external shell surface and shell membrane were detected in the infected hens from 1 to 5 dpi as compared with the control hens. In conclusion, this study confirmed that H9N2 AIV strain (A/Chicken/shaanxi/01/2011) infection is associated with severe lesions of the uterus and abnormal expression of CaBP-D28k mRNA in the uteri of the infected hens. The change of CaBP-D28k mRNA expression may contribute to the deterioration of the eggshell quality of the laying hens infected with AIV. It is noteworthy that the pathogenicity of H9N2 AIV strains may vary depending on the virus strain and host preference.